AB0967 IS THERE A DIFFERENCE IN PRESENTATION OF FEMALE AND MALE PATIENTS WITH JUVENILE SYSTEMIC SCLERODERMA. AN UPDATE FROM THE JUVENILE SYSTEMIC SCLERODERMA INCEPTION COHORT. WWW.JUVENILE-SCLERODERMA.COM. (June 2019) - Foeldvari, Ivan; Klotsche, Jens; Kasapcopur, Ozgur; Adrovic, Amra; Torok, Kathryn; Stanevicha, Valda; Sztajnbok, Flávio R.; Sakamoto, Ana Paula; Alexeeva, Ekaterina; Anton, Jordi; Katsikas, Maria; Smith, Vanessa; et al.
Abstract : Background: Juvenile systemic scleroderma (jSSc) is an orphan disease with a prevalence of 3 in 1 000 000 children (1). There are limited data published regarding the differences in clinical presentation of male and female patients with jSSc. The Juvenile Systemic Scleroderma Inception Cohort (JSSIC) is a multinational cohort with a prospective standardized assessment of the patients. The data regarding the difference in clinical characteristics at time of inclusion in the cohort are presented. Objectives: Evaluation of the differences in clinical presentation of male and female jSSc patients at the time of inclusion in the JSSIC. Methods: The JSSIC is a prospective multicentre registry of patients with jSSc, who fulfil the adult classification criteria (2), and presented the first non-Raynaud symptoms before 16 years old and were younger than 18 years old at the time of inclusion in the cohort. Patients characteristics at time of inclusion in the cohort were evaluated. Results: As of 15 th of December 2018 120 patients are included in JSSIC. The great majority are female (80%). There were more female patients with CK elevation (29% vs 22%) and more female patients with Gottron papulae (25% vs 12%). The mean modified skin score was higher in males (18.6 vs 13.9). Sclerodactyly was more frequent in males (90% vs 76%). Active ulceration was present in 33% of males compared to 14% of females (p=0.026). FVC<80% occurred more often in males with 47% compared with 24% in females (p=0.018). Pulmonary hypertension was more common in females with 7% compared to 4% in males. Urine sediment changes were more common in males (8% vs 4%). Gastrointestinal involvement was more common in females (37% vs 29%). Contractures occurred more often in males with 62% compared with 46% in females. Tendon friction rub was observed in 21% of males and 3% of females (p=0.001). Physician global scores of disease activity and damage were higher in males with 48 for both assessments compared to 36 and 30 in females. Conclusion: Male patients with jSSc have a higher severity of disease, as it has been reported in adults. References: [1] Beukelman T, Xie F, Foeldvari I. Assessing the prevalence of juvenile systemic sclerosis in childhood using administrative claims data from the United States. Journal of Scleroderma and Related Disorders. 2018;3(2):189-90. [2] van den Hoogen F, Khanna D, Fransen J, Johnson SR, Baron M, Tyndall A, et al. 2013classification criteria for systemic sclerosis: an American College of Rheumatology/European Disclosure of Interests: Ivan Foeldvari Consultant for: Chugai, Novartis, Jens Klotsche: None declared, Ozgur Kasapcopur: None declared, Amra Adrovic: None declared, Kathryn Torok: None declared, Valda Stanevicha: None declared, Flávio R. Sztajnbok: None declared, Ana Paula Sakamoto: None declared, Ekaterina Alexeeva: None declared, Jordi Anton Grant/research support from: Grant/research support, consultant or speakers bureau from AbbVie, Alexion, Bristol-Myers Squibb, ChemoCentryx, Gebro, GlaxoSmithKline, Novartis, Novimmune, Pfizer, Roche, Sanofi and Sobi, Consultant for: Grant/research support, consultant or speakers bureau from AbbVie, Alexion, Bristol-Myers Squibb, ChemoCentryx, Gebro, GlaxoSmithKline, Novartis, Novimmune, Pfizer, Roche, Sanofi and Sobi, Speakers bureau: Grant/research support, consultant or speakers bureau from AbbVie, Alexion, Bristol-Myers Squibb, ChemoCentryx, Gebro, GlaxoSmithKline, Novartis, Novimmune, Pfizer, Roche, Sanofi and Sobi, Maria Katsikas: None declared, Vanessa Smith: None declared, Tadej Avcin: None declared, Rolando Cimaz: None declared, Mikhail Kostik: None declared, Thomas Lehman: None declared, Walter Alberto Sifuentes-Giraldo: None declared, Simone Appenzeller: None declared, Mahesh Janarthanan: None declared, Monika Moll: None declared, Dana Nemcova: None declared, Maria Jose Santos: None declared, Amara Nassar: None declared, Cristina Battagliotti: None declared, Lillemor Berntson: None declared, Blanca Bica: None declared, Juergen Brunner: None declared, Patricia Costa Reis: None declared, Despina Eleftheriou: None declared, Liora Harel: None declared, Gerd Horneff: None declared, Tilmann Kallinich Grant/research support from: Novartis, Speakers bureau: Sobi, Roche, Novartis, CLB, Dragana Lazarevic: None declared, Kirsten Minden Consultant for: AbbVie, Susan Nielsen: None declared, Farzana Nuruzzaman: None declared, Anjali Patwardhan: None declared, Yosef Uziel: None declared, Nicola Helmus: None declared